Depression, Antidepressants, and Bone Health in Older Adults: A Systematic Review. Issue 8 (15th July 2014) - Gebara, Marie Anne; Shea, Marcie L. O.; Lipsey, Kim L.; Teitelbaum, Steven L.; Civitelli, Roberto; Müller, Daniel J.; Reynolds, Charles F.; Mulsant, Benoit H.; Lenze, Eric J.
<x xml:space="preserve">Abstract</x> Objectives To examine the association between depression, antidepressant use, and bone health in older adults and the implications for treatment. Design Systematic review. Setting All studies that measured depression or antidepressant exposure and bone mineral density (BMD). Participants Adults aged 60 and older. Measurements Age, site of BMD measurement using dual‐energy X‐ray absorptiometry (DXA), measure of depression or depressive symptoms, association between BMD changes, and depression or antidepressant use. Results Nineteen observational studies met the final inclusion criteria; no experimental studies were found. Several cross‐sectional and longitudinal studies found that depression or depressive symptoms were associated with a decrease in BMD. Few studies and only two longitudinal studies addressed the association between serotonin reuptake inhibitor (SRI) antidepressant use and a decrease in BMD and they had conflicting results. Conclusion Depression and depressive symptoms are associated with low bone mass and accelerated bone loss in older adults; putative mechanisms underlying this relationship are discussed. There is insufficient evidence that SRI antidepressants adversely affect bone health. Thus, a change in current recommendations for the use of antidepressants in older adults is not justified at the present time. Given the high public health significance of this question, more studies are required to determine whether (and in whom) antidepressants may be deleterious for bone health.